Remoción del carbono orgánico disuelto en humedales piloto de flujos subsuperficial y superficial (2010)
ABSTRACT: To compare removal of dissolved organic carbon (doc) obtained with pilot wetlands of subsuperficial flow (phss) and superficial flow (phs), with Phragmites australis as treatment alternatives for domestic residual waters of small communities and rural areas. Methodology: an exploratory and experimental study was carried out adding 100,12 mg/L of dissolved organic carbon to synthetic water contaminated with Chlorpyrifos in order to feed the wetlands. A total amount of 20 samples were done, 16 of them in four experiments and the other ones in the intervals with no use of pesticides. Samples were taken on days 1, 4, 8, and 11 in the six wetlands, three of them subsuperficial, and three of them superficial. The main variable answer was dissolved organic carbon, measured in the organic carbon analyzer. Results: a high efficiency in the removal of doc was obtained with the two types of wetlands: 92,3% with subsuperficial flow and 95,6% with superficial flow. Such a high removal was due to the interaction between plants, gravel and microorganisms. Conclusion: although in both types of wetlands the removal was high and similar, it is recommended to use those of subsuperficial flow because in the superficial ones algae and gelatinous bio-films are developed, which becomes favorable to the development of important epidemiologic vectors in terms of public health.